ASSESSMENT OF FACTORS INFLUENCING BEEKEEPERS' ACTIVITIES IN LATGALE (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
There are approximately 3,400 beekeeping farms in Latvia with more than 100,000 registered bee colonies. Most of them are family businesses and are not united in cooperatives, organizations or producer groups. This study analyzes the operation of beekeeping farms in Latgale, evaluating the factors that affect their productivity and development. The aim of the study is to determine the relationship between beekeeping practices, farm size, education level, marketing strategies, bee diseases, climate conditions and other factors, and how they affect honey yields and farm openness in Latgale (Latvia). The study used correlation analysis between different factors. The results showed that professional beekeepers, for whom beekeeping is the main source of income, are more open to tourism, have registered with the Food and Veterinary Service (PVD), change queen bees in a controlled manner, sow nectar plants, have developed product identification marks, have a higher number of honey extractions per season, and on average collect more than 50 kg of honey from one colony per season. It was also found that the beekeeper's level of education and the farm's visibility have a positive impact on honey yield and sales price. For example, more educated beekeepers produce 15% more honey per colony on average, and their honey sales price is 10% higher. In addition, it was found that beekeepers who have fewer problems with neighbors using pesticides tend to have higher honey yields. These findings could be useful for developing recommendations for the sustainable development of the beekeeping industry in Latgale.